2017
DOI: 10.1103/physreve.96.032412
|View full text |Cite
|
Sign up to set email alerts
|

Transitions in optimal adaptive strategies for populations in fluctuating environments

Abstract: Biological populations are subject to fluctuating environmental conditions. Different adaptive strategies can allow them to cope with these fluctuations: specialization to one particular environmental condition, adoption of a generalist phenotype that compromise between conditions, or population-wise diversification (bet-hedging). Which strategy provides the largest selective advantage in the long run depends on the range of accessible phenotypes and the statistics of the environmental fluctuations. Here, we a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
42
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Since a phenotype can be close to only one of the archetypes, there is a trade-off between the fitness values in different environments. In this case, the shape of the phenotype distribution can be understood by analyzing the geometry of the "fitness set" [8,40].…”
Section: Analytic Limitsmentioning
confidence: 99%
See 2 more Smart Citations
“…Since a phenotype can be close to only one of the archetypes, there is a trade-off between the fitness values in different environments. In this case, the shape of the phenotype distribution can be understood by analyzing the geometry of the "fitness set" [8,40].…”
Section: Analytic Limitsmentioning
confidence: 99%
“…(A10). By locating the point within the extended fitness set that maximizes the long-term growth rate, Λ = µ p µ log f µ , one can find the optimal phenotypic response and the phenotype distribution [8].…”
Section: Analytic Limitsmentioning
confidence: 99%
See 1 more Smart Citation
“…the persistence of a sub-population of resistant but slow-growing bacteria within a popula-tion subject to high doses of antibiotics [15,16]. Starting with [17], several mathematical models have shown that switching between different phenotypes at the individual cell level can be advantageous in rapidly changing conditions, depending essentially on (i) the statistics of environmental fluctuations and (ii) the specific coupling between the environment and the allowed phenotypes [18][19][20][21][22][23][24][25][26][27][28]. Such models capture the physical and mathematical complexity of these systems starting from minimal assumptions about the environment and/or the space of feasible phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Studying the evolutionary rescue of a population in 14 a gradually deteriorating environment requires accounting for simultaneous continuous time variations of fitness, 15 population size and population composition, which makes it complex. Varying patterns of selection have recently 16 been the focus of significant interest, mainly in the case of switches between different environment states, highlighting 17 their strong effect on evolution [22][23][24][25][26][27][28][29][30][31][32][33][34][35]. Despite its practical relevance, the case of a continuously varying fitness has 18 been comparatively less studied, with a focus on stabilizing selection [36,37] or on the fate of a single beneficial 19 mutation [1][2][3].…”
mentioning
confidence: 99%